Optimal Control Problem for Switched System with the Nonsmooth Cost Functional - Shahlar Meherrem; Rufan Akbarov (Abstract and Applied Analysis)
We examine the relationships between lower exhausters, quasidifferentiability (in the Demyanov and Rubinov sense), and optimal control for switching systems. Firstly, we get necessary optimality condition for the optimal control problem for switching system in terms of lower exhausters. Then, by using relationships between lower exhausters and quasidifferentiability, we obtain necessary optimality condition in the case that the minimization functional satisfies quasidifferentiability condition.